Study of Mental Health Status of the Resident Physicians in China During the COVID-19 Pandemic - Jia, Shuang-Zhen; Zhao, Yu-Zhen; Liu, Jia-Qi; Guo, Xu; Chen, Mo-Xian; Zhou, Shao-Ming; Zhou, Jian-Li (Frontiers in Psychology, 2022)
Objective: Investigating the mental health status of Chinese resident physicians during the 2019 new coronavirus outbreak. Methods: A cluster sampling method was adopted to collect all China-wide resident physicians during the epidemic period as the research subjects. The symptom Checklist-90 self-rating scale was used to assess mental health through WeChat electronic questionnaires. Results: In total, 511 electronic questionnaires were recovered, all of which were valid questionnaires. The negative psychological detection rate was 93.9% (480/511). More than half of the Chinese resident physicians had mild to moderate mental unhealthy symptoms among the symptoms on the self-rating scale, and a few showed asymptomatic or severe mental unhealthy state; In details, the detection rate of abnormality was 88.3% (451/511), obsessive-compulsive symptoms was 90.4% (462/511), sensitive interpersonal relationship was 90.6% (463/511), depression abnormality was 90.8% (464) /511), anxiety abnormality was 88.3% (451/511), hostility abnormality was 85.3% (436/511), terror abnormality was 84.9% (434/511), paranoia abnormality was 86.9% (444/511), psychotic abnormalities was 89.0% (455/511), and abnormal sleeping and eating status was 90.8% (464/511). The scores of various psychological symptoms of pediatric resident physicians were significantly lower than those of non-pediatrics (P<0.05). Conclusions: The new coronavirus epidemic has a greater impact on the mental health of Chinese resident physicians.